Minimally invasive approaches for the treatment of inflammatory bowel disease - Zoccali, Marco (Baishideng Publishing Group Co., Limited, 2012)
Despite significant improvements in medical management of inflammatory bowel disease, many of these patients still require surgery at some point in the course of their disease. Their young age and poor general conditions, worsened by the aggressive medical treatments, make minimally invasive approaches particularly enticing to this patient population. However, the typical inflammatory changes that characterize these diseases have hindered wide diffusion of laparoscopy in this setting, currently mostly pursued in high-volume referral centers, despite accumulating evidences in the literature supporting the benefits of minimally invasive surgery. The largest body of evidence currently available for terminal ileal Crohn’s disease shows improved short term outcomes after laparoscopic surgery, with prolonged operative times. For Crohn’s colitis, high quality evidence supporting laparoscopic surgery is lacking. Encouraging preliminary results have been obtained with the adoption of laparoscopic restorative total proctocolectomy for the treatment of ulcerative colitis. A consensus about patients’ selection and the need for staging has not been reached yet. Despite the lack of conclusive evidence, a wave of enthusiasm is pushing towards less invasive strategies, to further minimize surgical trauma, with single incision laparoscopic surgery being the most realistic future development.